Preparation and characterisation of polymer microparticles with varying morphologies with application in drug delivery - Braz de Sousa, Ana Letícia (2020)
Polymer-based particles of varied porosity, roughness and morphology have been prepared by many different methods towards biomedical applications. One of their most important applications is as degradable and targeted drug delivery systems, with reduced toxicity and side effects compared to their solid counterparts. Polymeric carriers loaded with chemotherapeutic agents have been applied in the treatment of glioblastoma (brain cancer, GBM) in an attempt to overcome the systemic toxicity, low drug solubility and poor efficacy of current treatments. In this work, polymeric microparticles (MPs) of poly(lactide) (PLA) and poly (lactide-co-glycolide) (PLGA) of various controlled morphologies have been developed with the capability to deliver a sustained release system loaded with cancer therapeutics against GBM cell proliferation and growth. In experimental Chapter 2 a family of different porous polymeric microparticles with controlled size were produced via single emulsion processing, incorporating a porogen. The produced porous PLA and PLGA particles were determined to be in the size range 34 to 320 m and exhibited homogeneous pore distribution throughout their particle structures. Particles encapsulated with dye exhibited encapsulation efficiency (EE) up to 21.6 + 5.4%, whereas particles encapsulated with drug exhibited EE up to 56 + 41%. Highly porous PLA particles (particle type C in this work) encapsulated with sodium chloride methotrexate and non-porous PLA particles (particle type A) and non-porous PLGA particles (particle type A’) encapsulated with docetaxel showed a significant difference in terms of therapeutic release in comparison to the other morphologies due the difference in the particle morphology and hydrophicility of the drug entrapped in the polymeric matrix(p>0.05). Particles alone and free drug were subsequently tested in vitro to test their toxicity at 24h. Particles alone exhibited a lack of toxicity and drugs alone showed a limited specificity for GBM cells (U87 cell line). The multi-therapy paste formulations including therapy 2 (PLGA MPs, PLGA-PEG matrix and DTX) and therapy 5 (PLA MPS and ETP, PLGA-PEG matrix and DTX) showed a significant difference when compared with control 1(PLA MPs alone), control 2 (PLGA MPs alone) and control 3 (PLGA-PEG matrix alone) over the 30-day investigation period (p<0.0001). In experimental Chapter 3, polymeric tablets were developed by mixing spherical PLA and PLGA MPs with non-spherical PLGA/polyethylene glycol (PEG) particles to achieve controlled and sustained release, and prolong the treatment against U87 cells. Mid porous PLA particles (particle type B) loaded with Nile Blue (NB) showed significant difference compared to non-porous PLA particles (particle type A), non-porous PLGA particles (particle type A’) and mid porous PLGA particles (particle type B’) (p<0.0001). Furthermore, these PLA and PLGA particles mentioned above exhibited controlled and sustained release over time, whereas the PLGA-PEG matrix exhibited burst release. U87 cells were subsequently treated with therapy 5 (tablet formulations), which demonstrated continuous reduction in cell viability over a 30-day period (p<0.0001). In conclusion, it is shown that polymeric MPs varying in their morphology have different surface areas and degradation rates, strongly influenced by the level of particle porosity. The release rate of active components is correlated with polymeric matrix composition and drug hydrophobicity. Porous polymeric carriers are a useful strategy for the controlled sustained release of active components such as chemotherapeutic drugs promoted by the slow release of dye and drugs. The development of polymeric paste and tablets herein prolonged the drug release from a PLGA-PEG matrix. Importantly, the tablet formulations (therapy 5) developed in this work can potentially control the proliferation and growth of U87 cells.